A portable solar irradiance meter / Hafizuddin Mohd Hariri - Mohd Hariri, Hafizuddin (2013)
This thesis presents a method of measuring the solar irradiance called a Portable Solar Irradiance Meter. The proposed technique helps to design simple, complex and low cost equipment. Same like other meter, this technique also have a same function which is to measure the solar irradiance in W/m2 . Due to the factor of cost of the sensor, a Portable Solar Irradiance Meter using microcontroller PIC 16F877A is designed. Instead of using other equipment's such as sunshine recorder, pyranometer and pyrheliometer, a portable solar irradiance meter will also have the same functions with a low cost and simpler. On this project, a solar cell is used as a sensor to generate electric power where the energy from the sun will be converted into a flow of electrons. The solar cell is then been connected to auxiliary circuit as to amplify the current drawn from solar cell and to convert its current into voltage. All the analog output from auxiliary circuit become as input to microcontroller. PIC 16F877A was used in this project as to process all the output from solar cell before send it to information window (display). The information window is available to display the solar irradiance in W/m . Based on the result, the Designed Meter successfully measures the solar irradiance in W/m2 . All the data obtained from this project been tabulated in performance comparison table as to compared with Megger Meter and shows very low error at below 12%. From the system performance graph, it is clearly shows that the system designed almost has similarity with Megger Meter in irradiance measurement.